REGIONAL DIVERSITY OF THE TOURISM FUNCTION IN POLAND (Research Bulletins of the Faculty of Economic Sciences, 2023)
The main goal of the undertaken research is to identify and assess the diversity of the tourism function in Poland in regional terms in 2021, as well as to identify regions with untapped tourist potential. The level of the tourist function was determined using a synthetic indicator, using the non-return method - based on partial indicators (Baretje-Defert index, accommodation base density index, Schneider index, Charvat index, percentage of economic entities in section I 55). The data comes from the Local Data Bank of the Central Statistical Office. On the basis of the results, the voivodships were divided into four classes with different levels of tourism function: class I – high level (West Pomeranian, Pomeranian, Małopolskie), class II – medium level (Warmińsko-Mazurskie, Dolnośląskie), class III – low level ( kujawsko-pomorskie, lubuskie, mazowieckie, podkarpackie, śląskie, świętokrzyskie), class IV – very low level (lubelskie, łódzkie, opolskie, podlaskie and wielkopolskie). In some voivodships, the existing tourist values are poorly used.
Keywords: tourism function, tourism function indicators, voivodships, regions